2021
DOI: 10.1097/mop.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coronavirus disease 2019 on newborns

Abstract: Purpose of review To evaluate the available literature regarding effects of coronavirus disease 2019 (COVID-19) on newborns, ranging from effects related to in utero and perinatal exposure to maternal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, to pandemic-related stress and socioeconomic changes. Recent findings Several large studies and national registries have shown that the risk of vertical transmission from SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Maternal exposure to microbial infection or immune activation during pregnancy has a long‐term impact on the development of the fetus after birth. Early research data show that the generation born during the pandemic of infectious diseases is at developmental risk 10 . The infection of pregnant women with viruses, such as rubella, respiratory tract infection, influenza, and bacterial infection, is a risk factor for numerous neurological and psychiatric disorders in their offspring 11–14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal exposure to microbial infection or immune activation during pregnancy has a long‐term impact on the development of the fetus after birth. Early research data show that the generation born during the pandemic of infectious diseases is at developmental risk 10 . The infection of pregnant women with viruses, such as rubella, respiratory tract infection, influenza, and bacterial infection, is a risk factor for numerous neurological and psychiatric disorders in their offspring 11–14 .…”
Section: Discussionmentioning
confidence: 99%
“…Early research data show that the generation born during the pandemic of infectious diseases is at developmental risk. 10 The infection of pregnant women with viruses, such as rubella, respiratory tract infection, influenza, and bacterial infection, is a risk factor for numerous neurological and psychiatric disorders in their offspring. [11][12][13][14] For a subset of women, maternal infection may be an inducement, leading to an altered trajectory of fetal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19), also known as SARS-CoV-2, has been shown to have numerous effects on maternal and neonatal outcomes, including increased rates of adverse maternal and neonatal outcomes such as an increased rate of a preterm birth, cesarean section, intrauterine growth restriction, low birthweight, hypertensive disorders of pregnancy, thrombotic events, fetal distress, APGAR scores < 7, NICU admission, stillbirth, and maternal and neonatal death [ 4 , 5 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In the present study, we demonstrated a significant difference between the mode and timing of delivery between the two maternal groups.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has been shown to have adverse maternal and neonatal outcomes, including increased rates of preterm births, cesarean sections, intrauterine growth restrictions, low birthweights, hypertensive disorders of pregnancy, thrombotic events, fetal distress, APGAR scores < 7, NICU admissions, stillbirths, and maternal and neonatal deaths [ 4 , 5 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The increased rate of preterm births has been affected by increased maternal indications for delivery, such as worsening COVID-19 infection and increased rates of hypertensive disorders of pregnancy [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many aspects of SARS-CoV-2 effect on pregnant woman and the effects of COVID-19 on the fetus remain insufficiently studied. This first of all refers to the effect of coronavirus disease of a pregnant woman on the developing fetus and, later, on the newborn [6,15]. The effect of COVID-19 during pregnancy on the parameters of umbilical cord blood (UCB) remains unexplored.…”
mentioning
confidence: 99%